Relevant factors affecting nurse staffing: a qualitative study from the perspective of nursing managers - Li, Gege; Wang, Waner; Pu, Jiangfeng; Xie, Zhanghao; Xu, Yixuan; Shen, Tiemei; Huang, Huigen (Frontiers in Public Health, 2024)
Objective To understand the current situation of nursing manpower allocation, explore the factors affecting nurse staffing, improve nurse staffing level, and provide reference for better formulation of nursing human resources staffing standards. Methods A descriptive research method was used to conduct semi-structured interviews with 14 nursing managers. The data were analyzed and refined by content analysis. The sample size was subject to content saturation. Results Nine themes and twenty sub-themes of influencing factors for nursing staffing were identified across four levels: hospital level, department level, patient level, and nurse level. Conclusion Hospital and department managers need to comprehensively consider the factors of affecting nurse staffing. Adopting multidimensional optimization measures, improving relevant systems, optimizing nurse structure, and establishing flexible and mobile nurse database to cope with public emergencies, so as to effectively improve nurse staffing and nursing service quality.